Ursolic acid attenuates oligospermia in busulfan-induced mice by promoting motor proteins - Dong, Jin; Ye, Taowen; Dong, Yanli; Hui, Jie; Wang, Xiaorong (PeerJ, 2024)
Background Oligospermia is one of the most common reasons for male infertility which is troubling numerous couples of child-bearing age. This investigation scrutinizes the implications and mechanistic underpinnings of ursolic acid’s effect on busulfan-induced oligospermia in mouse models. Methods A singular intraperitoneal injection of busulfan at a dosage of 30 mg/kg induced oligospermia. Two weeks subsequent to this induction, mice were subjected to various dosages of ursolic acid (10, 30, and 50 mg/kg body weight, respectively) on a daily basis for four consecutive weeks. Following this treatment period, a meticulous analysis of epididymal sperm parameters, encompassing concentration and motility, was conducted using a computer-assisted sperm analysis system. The histopathology of the mice testes was performed utilizing hematoxylin and eosin staining, and the cytoskeleton regeneration of the testicular tissues was analyzed via immunofluorescent staining. Serum hormone levels, including testosterone, luteinizing hormone, and follicle-stimulating hormone, as well as reactive oxygen species levels (inclusive of reactive oxygen species and malondialdehyde), were gauged employing specific enzyme-linked immunosorbent assay kits. Differentially expressed genes of testicular mRNA between the oligospermia-induced group and the various ursolic acid treatment groups were identified through RNA sequencing analysis. Results The results revealed that a dosage of 50 mg/kg ursolic acid treatment could increase the concentration of epididymal sperm in oligospermia mice, promote the recovery of testicular morphology, regulate hormone levels and ameliorate oxidative damage. The mechanism research results indicated that ursolic acid increased the expression level of genes related to motor proteins in oligospermia mice.
Keywords: Ursolic acid; Oligospermia; Busulfan; Serum hormone; Motor proteins